An Evaluation of the Keeping Well at Home Booklet. (20th October 2021) - Money, A; McDermott, J; Littlewood, A; Todd, C
Abstract: Background: In the first wave of COVID-19, the UK Government relied heavily on digital channels to provide information to the public. This disproportionately excluded older people - one of the groups with least access to (or experience of) using the internet. Approximately 11.5 million people in the UK lack digital skills and 4.8 million people never go online, with around half (51%) of these being aged over 65. The Greater Manchester (GM) response was to work collaboratively with a number of key Ageing groups to develop Keeping Well at Home, a booklet providing evidence based health and wellbeing information and advice for older people during COVID-19 restrictions. Methods: An evaluation of the booklet was undertaken during summer 2020 by the Healthy Ageing team at the Applied Research Collaboration GM. As national restrictions on movement remained in place at the time, a postal questionnaire was distributed to a sample of older adults in GM. Results: Nearly 500 questionnaires were returned. The response was overwhelmingly positive; 92% found the information helpful; 90% agreed the booklet would help older people stay healthy during lockdown; 74% had used the home exercises section; 78% found the tips for keeping their mind well helpful. Around 50% of respondents did not have internet access. Paper based resources was the preferred choice for 92% of respondents with only 6% opting for digital versions. Conclusions: The evidence from the evaluation challenges the growing trend towards communicating just through digital channels, and emphasises the need for tailored paper-based materials for older adults. The Keeping Well at Home booklet also shows the value of working with older adults to ensure the content and design are inviting to readers. Information, support and services must be made available in an offline equivalent and proactively disseminated to reach those who otherwise would not have access to it. Key messages: Print-based communications are preferred over digital for some groups; ensuring inclusivity is critical as the 'digital by default' approach excludes large numbers of our population. Including target group representatives as co-editors to advise on content and stylistic design is key to ensure content is relevant and useful.